Kajian Multiperspektif Keperawatan Medikal Bedah Berbasis Literature Review - Dwi Harianto (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The combination of nursing, medical, and surgical sciences is often integrated into medical surgical nursing science. Medical surgical nursing is a branch of nursing that combines medical and surgical sciences to provide comprehensive care to patients. This is because nurses are required to have knowledge and technical skills that are adaptive to today's health world. In order to optimize this, a holistic study is needed to identify gaps that need to be fixed, both in terms of practice, development, and education. However, there has been no research that examines these things. Therefore, this study aims to explain the multi-perspective study of medical surgical nursing with a literature review. The method used is a literature review with various literatures from Google Scholar. The results of the study show that most of the scientific literature that studies medical surgical nursing has supported studies from the perspective of development, assessment, and education. Some of this literature can be used as a basis for reviewing and evaluating the world of surgical nursing more comprehensively so that it can be improved according to the findings of field research.